IMMU-27. IMMUNE CHECKPOINT BLOCKADE OF EX VIVO EXPANDED T CELLS FOR USE IN ADOPTIVE CELLULAR THERAPY (ACT) FOR GLIOBLASTOMA. (11th November 2019) - Ogando-Rivas, Elizabeth; Yang, Changlin; Castillo, Paul; Dechkovskaia, Anjelika; Mitchell, Duane
Abstract: BACKGROUND: Despite aggressive treatments, GBM continues to have unacceptably high mortality rates. Immune-checkpoint blockade and ACT have shown excellent results in other solid tumors, especially in melanoma. Unfortunately, these results have not been extrapolated to GBM. We have developed a novel platform for ACT using tumor mRNA-pulsed dendritic cells(DCs) to in-vitro expand polyclonal populations of tumor-reactive T-cells. This platform has shown promising effects in preclinical brain tumor models ( Flores et al OncoImmunology 2015, Wildes et al CCR 2018, Flores et al NatureComm 2018 ) and being evaluated in clinical trials at UF Health ( NCT02465268, NCT03334305 ). STUDY OBJECTIVE: Evaluate whether immune-checkpoint blockade during ex-vivo expansion of antigen-specific T-cells impact their use in ACT. METHODS: CMVpp65 was used as model antigen for in-vitro activation of T-cells. Mature pp65 mRNA-pulsed DCs from CMV+ healthy donors were co-cultured with T-cells in IL2-containing medium for 15days. We tested four checkpoint inhibitor groups: PD1(n= 6), PDL1(n= 4), TIM3(n= 7) and PD1+TIM3(n= 6) that were compared with non-blockade group, respectively. Checkpoint blockade was performed every 3days. T-cell proliferation, immune-phenotyping, and IFN-g release were analyzed. RESULTS: Cell proliferation was lower in all the blockade groups but significantly lower in the TIM3 (p= 0.03 ) and TIM3+PD1 (p= 0.01 ) blockade groups. TIM3 expression was significantly lower in the TIM3 (p= 0.006 ) and PD1+TIM3 blockade groups (p= 0.0001 ). There was a trend of reduced pp65 tetramer positive in the TIM3 and PD1+TIM3 blockade groups (PD1+TIM3 subgroup at 3mcg/mL, p= 0.02 ) and lower INFg release in the TIM3 and PD1+TIM3 blockade groups. CONCLUSION: The exact role of checkpoints during expansion of T-cells for ACT is not well understood. In our study checkpoint blockade with PD-1 or TIM-3 alone or in combination did not enhance T-cell expansion or function, in fact, appeared to have an inhibitory effect on measured parameters. Our results suggest that TIM-3 may have an activating role in our system.